Textual Metafunction in English Translation of The Noble Qur’an’s Surah ‘Abasa - Irdayanti, Irdayanti; Barus, Jumat; Muna, Hayatul (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2022)
The purposes of this research are to identify the types of theme used in translation Qur’an Surah ‘Abasa and to derive the dominant type of theme used in translation Qur’an Surah ‘Abasa. Here, the researcher applied descriptive qualitative approach. The data of this research were clauses in English translation of Qur’an Surah ‘Abasa which collected from Translation of the Meanings of The Noble Qur'an in the English Language by Dr. Muhammad Taqiuddin al-Hilali and Dr. Muhammad Muhsin Khan. The researcher used documentation technique as data collection technique in this study. In analyzing the data, the Interactive Model Technique of Miles, et. al., (2014) was employed in this study. The results of the research show the frequency and percentage of the types of theme used in the English translation of Qur’an Surah ‘Abasa. They are 55 Unmarked Topical Themes (49.55%), 34 Conjunction Textual Themes (30.63%), 20 Marked Topical Themes (18.02%), and 2 Polarity Adjunct Interpersonal Themes (1.80%). This finding showed that Unmarked Topical Theme is mostly used in the English translation of Qur’an Surah ‘Abasa because it explained a lot about nominal group and nominal group complex and it has a tendency to use subject as theme.